Analysis and interpretation of regional geophysical data in the Michipicoten (Wawa) Greenstone Belt, Superior Province in Canada (2023)
The project involved the construction of 2.5D forward gravity models, along transverse and longitudinal sections, relative to the identified geological structures. There was an analysis and modeling of public Regional Gravity and Magnetic data of the area, in order to investigate and understand the geometry and depth extent of the Wawa Greenstone Belt.